2016
DOI: 10.1016/j.chembiol.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Survey of Serine Hydrolase Activity in Mycobacterium tuberculosis Defines Changes Associated with Persistence

Abstract: SUMMARY The transition from replication to non-replication underlies much of Mycobacterium tuberculosis (Mtb) pathogenesis, as non- or slowly replicating Mtb are responsible for persistence and poor treatment outcomes. Therapeutic targeting of non-replicating populations is a priority for tuberculosis treatment, but few drug targets in non-replicating Mtb are currently known. Here, we directly measured the activity of the highly diverse and druggable serine hydrolases (SHs) during active replication and non-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
104
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 38 publications
(58 reference statements)
11
104
0
1
Order By: Relevance
“…8 The first site features a lysine in the P2 position, in agreement with the substrate preference we observed by MSP-MS and PS-SCL. The second cleavage appears to have many suboptimal amino acids in the P4–P4′ positions with the exception of glycine in the P1′ position.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…8 The first site features a lysine in the P2 position, in agreement with the substrate preference we observed by MSP-MS and PS-SCL. The second cleavage appears to have many suboptimal amino acids in the P4–P4′ positions with the exception of glycine in the P1′ position.…”
Section: Resultssupporting
confidence: 86%
“…M. tuberculosis Hip1 was produced as described previously, 8 and our initial studies revealed that it cleaved fluorogenic substrate WKLL-ACC with a k cat / K M value of 1.9 × 10 3 M –1 s –1 (Table 1). This substrate was designed to be cleaved by another cell envelope-associated Mtb protease, MarP, 10 and was unlikely to be optimal for Hip1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations